Olympic predictions - Johnson, K. N. (2004)
You find some summary tables of our predictions for the 2004 Summer Olympic Games in Athens. They draw upon the author`s calculations from the forthcoming paper in Social Science Quarterly, entitled "A Tale of Two Seasons: Participation and Medal Counts at the Summer and Winter Olympic Games".